EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DENGAN GUIDED NOTE TAKING PADA POKOK BAHASAN BANGUN DATAR DITINJAU DARI KEMANDIRIAN BELAJAR PADA SISWA SMP KELAS VII DI KOTA SURAKARTA TAHUN PELAJARAN 2013/2014 - Ambarwati, Dwi; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of research is to determine the effect of learning models on learning achievement viewed from students independence learning. The type of the research is a quasi-experimental. The population are the seventh grade students of junior high school at Surakarta. The sample are 268 students. Sampling is done by stratified cluster random sampling. Instruments which are used to collect data are achievement tests and questionnaire of students independence learning. Hypothesis test is two-way analysis of variance with unbalanced cells. The results of this research are as follows: 1) the TPS-GNT learning model gives better learning achievement than TPS and direct learning model, and TPS learning model gives better learning achievement than direct learning model. 2) Â the students with high independence learning have better learning achievement than students with medium and low independence learning, and the students with medium independence learning have better learning achievement than students with low independence learning. 3) in each Â learning model, the students with high, medium and low independence learning have the same learning achievement. 4) in the high independence learning, students with TPS-GNT, TPS and direct learning model have the same learning achievement, but in the medium and low independence learning, students with TPS-GNT learning model have better learning achievement than students with direct model, students with TPS-GNT and TPS learning model have the same learning achievement and students with TPS and direct learning model have the same learning achievement.Keywords: Think Pair Share (TPS), Guided Note Taking Â (GNT), Independence Learning